Predictive value of the CT Scan in comparison with laparotomy in the diagnosis of peritonitis in COVID-19 patients - Masoudi, Naser; Rezaei, Seifollah; Davoudi, Nader (Journal of Shahrekord University of Medical Sciences, 2025)
Background and aims: The present study aimed to investigate the predictive value of the computed tomography (CT) scan in diagnosing peritonitis compared to laparotomy in COVID-19 patients. Methods: This study evaluated 11 COVID-19 patients with suspected peritonitis. All patients underwent laparotomy because of free air detected within the abdomen on CT scans. Results: The results demonstrated 9 (81.8%) true positive cases that were positive for peritonitis on both laparotomy and the CT scan and 2 (18.2%) false positive cases that were positive for peritonitis on the CT scan but negative for peritonitis on laparotomy. The sensitivity, specificity, and accuracy of CT scans in diagnosing peritonitis were 100%, 81.8%, and 81.8%, respectively, and 81.8% of peritonitis cases were correctly diagnosed on CT scans. Conclusion: Based on the positive predictive value, 81.8% of peritonitis cases were correctly diagnosed on a CT scan. The overall mortality rates for patients with and without peritonitis were 4.44% and 50%, respectively.